A Review on The Physical, Milling Quality and Physicochemical Characteristic of Hipa 6 Jete and Hipa 7 - Shinta Dewi Ardhiyanti; Siti Dewi Indrasari (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2020)
Up to now the Agriculture Ministry of Republic of Indonesia has released 19 varieties of hybrid rice. Hipa 6 Jete and Hipa 7 varieties are two of them. Hybrid rice is a group of rice plants formed from first generation individuals (F1) derivative of a combination of crossing between certain elders. Hybrid rice superior varieties has a higher yield potential than inbred superior varieties that dominate rice cultivation areas. Rice quality is one of the factors that determine the level of consumer acceptance of a variety. The rice quality is influenced by several factors such as physical quality, cooking quality and taste quality. This paper aims to review the physical quality, milling quality and physical properties of Hipa 6 Jete and Hipa 7. The length of Hipa 6 Jete and Hipa 7 are long and the shape are slender. Based on the head rice and broken rice percentage both Hipa 6 Jete and Hipa 7 are met the medium 2 and 3 quality class (SNI 6128:2015). Based on the physicochemical characteristics both Hipa 6 Jete and Hipa 7 are classified as intermediate amylose content with soft gel consistency and with high intermediate gelatinization temperature. In cooling condition the cooked rice of Hipa 6 Jete and Hipa 7 are soft texture.